2018
DOI: 10.1016/j.arthro.2018.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Return to Sport After Surgical Treatments of the Acromioclavicular Joint Dislocation Seems to Be Almost Perfect in the Literature

Abstract: Systematic reviews identify completed studies that address a research question and evaluate the results of these studies to arrive at conclusions about a body of research. They should be encouraged because the findings, with power enhanced by the larger sample size available from the combined studies, often represent an important scientific contribution. The systematic review findings also can be a useful background for developing practice guidelines in the future. One of limitations of this approach is a risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…A systematic review 16 investigating the effect of surgical management for ACJ dislocations has found that many papers present excellent return-to-sport rate but at longer times that may affect career goals. This resulted in an editorial 18 that suggested publication bias may be affecting the outcomes and that the outcome of interest often goes unreported. For this reason, we not only investigated the time taken to return to sport and on-field performance but also used an outcome measure that was sensitive and specific to measuring changes in the ACJ-injured population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A systematic review 16 investigating the effect of surgical management for ACJ dislocations has found that many papers present excellent return-to-sport rate but at longer times that may affect career goals. This resulted in an editorial 18 that suggested publication bias may be affecting the outcomes and that the outcome of interest often goes unreported. For this reason, we not only investigated the time taken to return to sport and on-field performance but also used an outcome measure that was sensitive and specific to measuring changes in the ACJ-injured population.…”
Section: Discussionmentioning
confidence: 99%
“…27 Grading of ACJ injuries should be made in comparison with the uninjured side. 18 An addition to the Rockwood classification was introduced to distinguish between horizontally stable (type IIIA) and unstable (type IIIB) injuries in the anteroposterior plane. 5 Basamania 39 has initiated discussion of so-called medial ACJ instability where the acromion is pushed in under the lateral clavicle in cross-body and resisted external rotation activities that are seen in sport with "fending away" movements, which are critical to AFL football.…”
mentioning
confidence: 99%
See 2 more Smart Citations